27‐3: Improved Device Performance for Inkjet Printed OLEDs via Interfacial Mixing Control. Issue 1 (25th September 2020) - Kim, Heung Gyu; Lee, Seung Mook; Shin, Dongwoo; Ha, Jaekook; Lee, Changhee
Abstract : Interfacial mixing between a solution‐processed hole transport layer and an emitting layer with thermal annealing (bake) process affects the device performance. We demonstrate that the moderate bake condition can improve device performance significantly; 133% increase in luminous efficiency and over 3 times enhancement in operation lifetime (T95) compared to the control device.